Is Ex Vivo Training before In Vivo Training Effective in Learning Gastric Endoscopic Submucosal Dissection? - Gyu Young Pih; Jung Su Lee; Ji Yong Ahn; Do Hoon Kim; Hee Kyong Na; Jeong Hoon Lee; Kee Wook Jung; Kee Don Choi; Ho June Song; Gin Hyug Lee; Hwoon-Yong Jung (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Background/Aims The learning curve is essential in endoscopic submucosal dissection (ESD) training to improve outcomes and reduce the risk of procedure-related complications. We compared the outcomes of gastric ESD in live pigs performed by inexperienced endoscopists with or without ex vivo training. Materials and Methods At the Olympus Medical Training and Education Center, nine endoscopists inexperienced in ESD were randomly divided into two groups (group A: ex vivo training followed by in vivo training; group B: in vivo training only), and they performed gastric ESDs. Results A total of 18 ESDs were performed. The en bloc resection rate was 88.9% (16/18), and the complete resection rate was 94.4% (17/18). The median specimen size was 2.5 cm in group A and 2.1 cm in group B (P=0.227). There was no significant difference in the procedure time between the two groups, except for the marking time (0′58″ vs. 2′58″, P=0.027). However, group A took a shorter time in dissecting the same area than group B (109 vs. 246 sec/cm2, P=0.083). Complication rates were not significantly different between both groups. Conclusions The procedure time during in vivo ESD training in pigs may be shortened by prior ex vivo training. However, the ex vivo model presented poor air inflation, unstable fixation, and excessive mucosal hardness for cutting. An advanced simulator or sufficient ex vivo training may be effective in training for the ESD procedure.